The Role Of Technological Innovation In Enhancing The Competitive Advantage Of Small Enterprises - ماخوس ديمه (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to clarify the role of technological innovation in its dimensions (innovation in product, innovation in operations, innovation in research and development) in enhancing the competitive advantage of small enterprises. Their number is 2312 workers, where the researcher obtained this number through the records of workers in administrative affairs, in order to know the role of technological innovation in improving competitive advantage. The researcher adopted the descriptive analytical approach within the framework of explaining the role of technological innovation dimensions in enhancing the competitive advantage. A main hypothesis was formulated that included three sub hypotheses. The researcher used the questionnaire to collect the data that was analyzed by Statistical package for social sciences. SPSS(20). The study reached a set of results, from which correlation between technological innovation in its dimensions (innovation in product, innovation in operations, innovation in research and development) and the promotion of competitive advantage, which means a statistically significant relationship between Technological innovation and promotion of competitive advantage The study recommended the necessity of promoting the adoption of competitive advantage in the project by increasing mutual trust between the organization and customers, and the organizations having a large number of technological innovations to achieve customer satisfaction.